2012
DOI: 10.1111/j.1530-0277.2011.01696.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Positive and Negative Monetary Feedback in Patients with Alcohol Dependence

Abstract: Impaired transfer performance suggests that ADP had problems applying their acquired knowledge in a new context. Potential relations to dysfunctions of specific brain structures and implications of the finding for therapy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Similar results were found in a recent study (Peles et al, 2014, under-review), which compared a larger sample of prolonged abstinence and methadone maintenance participants and show no differences in lifetime opiate usage. Moreover, prolonged abstinence individuals in this study reported younger age of onset Our findings are in line with other studies, which tested alcohol dependent patients (Máttyássy et al, 2012;Rustemeier et al, 2012). Similarly, these studies have shown that both alcohol dependent patients and healthy controls were equally able to acquire stimulus-outcome associations.…”
Section: Discussionsupporting
confidence: 95%
“…Similar results were found in a recent study (Peles et al, 2014, under-review), which compared a larger sample of prolonged abstinence and methadone maintenance participants and show no differences in lifetime opiate usage. Moreover, prolonged abstinence individuals in this study reported younger age of onset Our findings are in line with other studies, which tested alcohol dependent patients (Máttyássy et al, 2012;Rustemeier et al, 2012). Similarly, these studies have shown that both alcohol dependent patients and healthy controls were equally able to acquire stimulus-outcome associations.…”
Section: Discussionsupporting
confidence: 95%
“…There are many variations of the PST, including using different stimuli ( Waltz et al, 2007 ) smiling and frowning faces as feedback ( Aberg et al, 2015 , 2016 ; Gold et al, 2013 ; Jocham et al, 2011 ), using money as feedback ( Kunisato et al, 2012 ; Rustemeier et al, 2012 ), changing the number of pairs ( Doll et al, 2014 ), the probabilities of reward ( Doll et al, 2014 ; Evans and Hampson, 2015 ), the number of trials ( Cicero et al, 2014 ; Evans and Hampson, 2015 ), and the filtering criterion ( Evans and Hampson, 2015 ; Waltz et al, 2007 ). Small changes such as changes to the stimuli used, or changing the delay between action and feedback can have large effects on how this task works ( Foerde and Shohamy, 2011 ; Schutte et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The participants continued in the training phase until they reached a designated learning criterion or until 480 trials were completed. The learning criterion was choosing A over B in 70% of trials within a block as has been used in past research by other labs ( Wheeler and Fellows, 2008 ; Rustemeier et al, 2012 ). Some studies have adopted slightly different criteria for learning (e.g., 65% A in AB, 60% C in CD, and 50% E in EF; Frank et al, 2005 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have adopted slightly different criteria for learning (e.g., 65% A in AB, 60% C in CD, and 50% E in EF; Frank et al, 2005 ). However, we chose to use the AB criterion only, because learning to prefer A over B is the only prerequisite for successful performance during the test phase ( Rustemeier et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%